APEX Strategy Represented by Diels–Alder Cycloadditions—New Opportunities for the Syntheses of Functionalised PAHs. Issue 53 (28th August 2020) - Kurpanik, Aneta; Matussek, Marek; Szafraniec‐Gorol, Grażyna; Filapek, Michał; Lodowski, Piotr; Marcol‐Szumilas, Beata; Ignasiak, Witold; Małecki, Jan Grzegorz; Machura, Barbara; Małecka, Magdalena; Danikiewicz, Witold; Pawlus, Sebastian; et al.
Abstract: Diels–Alder cycloaddition of various dienophiles to the bay region of polycyclic aromatic hydrocarbons (PAHs) is a particularly effective and useful tool for the modification of the structure of PAHs and thereby their final properties. The Diels–Alder cycloaddition belongs to the single‐step annulative π‐extension (APEX) reactions and represents the maximum in synthetic efficiency for the constructions of π‐extended PAHs including functionalised ones, nanographenes, and π‐extended fused heteroarenes. Herein we report new applications of the APEX strategy for the synthesis of derivatives of 1, 2‐diarylbenzo[ghi]perylene, 1, 2‐diarylbenzo[ghi]perylenebisimide and 1, 2‐disubstituted‐benzo[j]coronene. Namely, the so far unknown cycloaddition of 1, 2‐diarylacetylenes into the perylene and perylenebisimide bay regions was used. 1, 2‐Disubstituted‐benzo[j]coronenes were obtained via cycloaddition of benzyne into 1, 2‐diarylbenzo[ghi]perylenes by using a new highly effective system for benzyne generation and/or high pressure conditions. Moreover, we report an unprecedented Diels–Alder cycloaddition–cycloaromatisation domino‐type reaction between 1, 4‐(9, 9‐dialkylfluoren‐3‐yl)‐1, 3‐butadiynes and perylene. The obtained diaryl‐substituted core‐extended PAHs were characterised by DFT calculation as well as electrochemical and spectroscopic measurements. Abstract : Extension please : The annulative π‐extension strategy represented by the Diels–Alder cycloaddition of acetylenes/benzyne and perylenes is able to generate π‐expanded structures with a broad spectrum of properties. A highly active system for the generation of benzyne and high‐pressure conditions were unprecedentedly used. DFT calculations, optical and electrochemical measurements were given for all the obtained products.